Book Review: E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35 - Cone, L. Winston (Journal of Asian and African Studies, 1975)
"E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35" published on 01 Jan 1975 by Brill.
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1975BS51300013, lens.org/075-687-014-811-491, pop00255 tex.type: [object Object] tex.unique-id: [object Object]
Keywords: book.review; dept.his

Review of Akwapim Handbook - Feinberg, H. M. (The International Journal of African Historical Studies, 1975)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1975BF75200071 tex.unique-id: [object Object]
Keywords: dept.his

Boredom and Treadmill of Doing - Tyler, RL (Humanist, 1975)
tex.unique-id: ISI:A1975AW55800006
Keywords: dept.his; ⛔ No DOI found